The Effect From Addition Of Collaleleaves (Centella asiatica .L) And Differenttechque Draying Metodh To Making Of Red Seaweed Nori (Gracilaria sp): Pengaruh Penambahan Daun Pegagan (Centella asiatica .L) Dan Perbedaan Teknik Pengeringan Pada Pembuatan Nori Rumput Laut Merah (Gracilaria sp) - rasmiati rasmiati; Nanik Suhartatik; Yannie Asrie Widanti (Fakultas Sains dan Teknologi Unisri, 2024)
Nori is one of food in the form of thin sheets. This study uses gotu kola leaves, and red seaweed as the basic ingredients for making nori. Red seaweed contains a large amount of amylopectin so that it has the potential to be used as nori, while gotu kola leaves have good fiber content. Except the fiber content, kola leaves (Centella asiatica .L) also content high antioxcidant as fenol, tanin and saponin. This study also uses drying with a cabinet dryer, room temperature and the sun. This study aims to determine the right formulation to produce gotu kola leaf nori which has high fiber content with variations in drying time. This research was conducted using a completely randomized design (CRD) method which consisted of 2 factors, namely the ratio of red seaweed and gotu kola leaves with variations in drying time. The first factor is the comparison of seaweed and gotu kola leaves (50:50, 40:60, and 30:70), while the second factor is the variation of nori drying time (cabinet drayer, room temperature and sun). The best chemical test results from fiber contant parameters were P3R3 with the results of 13.41% water content, 0.052 ash content, 21.18% crude fiber and 8.71 tensile strength. The best sensory test results were P3R3 with color test results of 3.64, gotu kola falvor 3.58, crunchiness 3.27, elasticity 3.27 and overall preference 3.85.